Grain Grading Standards in Feed Manufacturing - Herrman, Tim J.; Kuhl, Gerry (My University, 1997)
This publication explains the different factors used to assign a grain grade and how these factors may influence the processing performance and feeding value of the low-grade grain.
MF2034_1997_01
Keywords: MF2034; Crops; Equipment and structures; MF